Budaya Pelayanan Di Kantor Kecamatan Kurun Kabupaten Gunung Mas Provinsi Kalimantan Tengah - , Sri Putri Pratiwi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Kurun District is one of the districts in Gunung Mas, which organizes the tasks and functions as mandated Government Regulation No. 7 of 2008 about the Town. I. against the regulation then poured more into Regulation Regent Mount Mas number 10 in 2009 about the descriptions of the tasks in an Office District in Gunung Mas, applicable local Gunung Mas number 6 in 2008 about the Organization and The Working districts and Subdistricts in Gunung Mas as well as Document Dated February 25, Foreboding Sub 2011 about the description of the task. One common task Village Office Space is to provide a community service into the scope of its work. However, functioning or whether civic service in the Office of Town Past the one hanging with a bureaucratic culture in itself is seen from the values, traditions and symbols that are run are used. Is it the culture of service in the Office of Districtoriented to the community over the past already as a user of the services or beriorientasi to power? Interest in the Culture Ministry is finally stimulate interest author researching more about the Culture Ministry bureaucracy is the most dominant in the Office For Sub-district. Based on the results of the interview, observation and secondary data, it can be inferred that the values which become the basic concepts, beliefs, ideas, and assumptions about an organization that is used as a reference for setting the standards of conduct by the apparatus For Sub in General was still oriented to power. While the traditions that are run by the Subdistrict Office Space as the apparatus the custom which is often made that States and strengthen the values that are valid in the Organization, the purpose of what most considered important and essential role of the people in the Organization turns out not to be released from the values of power where there is recognition of the views of the leadership that holds the authority of power. Likewise with the symbols used by the past in the form of the word paratur Subdistrict, gestures, pictures, or objects that have special meaning within the Organization was still describing the culture of service oriented to power. With regard to the strength of the Culture Ministry is still oriented to power, where the influence of feudalism was still going on in the next Head Office environment, it is necessary to do an activity of learning and an introduction about the paradigm of service including a good service culture to the apparatus of the Office Space with the goal of keeping subdistrict of the District of better understanding about their function and duty as servants and for the community. Second, the study needs to be done appeals to the areas that have been successful or is considered successful in providing good service, so that learning and the introduction of the service and the Culture Ministry could be applied or adapted in the context of the local subdistrict of the past.